Plasmodium falciparum malaria cases detected for prompt treatment by rapid diagnostic tests in the Ho Teaching Hospital of the Volta Region of Ghana. Issue 3 (August 2018) - Dinko, Bismarck; Amakpa, Eric; Kweku, Margaret; Amoah, Paul; Tampuori, John; Adjuik, Martin; Awandare, Gordon A.; Deitsch, Kirk W.
Abstract: Background: Prompt diagnosis and effective treatment of malaria cases with efficacious drugs is an important strategy in the management and control of malaria in endemic populations. As part of a study investigating the factors modulating the development of Plasmodium falciparum gametocytes in the human host, we assessed the rate of RDT positivity of patients in different departments of the Ho Teaching Hospital and the relation with age and anaemia. Materials and methods: Eight-hundred and ten individuals attending clinic at various departments within the Ho Teaching Hospital were screened for malaria antigenaemia using RDT as a point-of-entry investigation. RDT positive individuals were immediately treated for malaria whereas RDT negative individuals were treated for other ailments. Haematological analyses were performed for 69 of these patients and the relationship between RDT results and haemoglobin levels were investigated. Results: The overall RDT positivity rate was 19.8% (160/810) of all individuals screened. There was no significant difference in the haemoglobin levels of RDT-positive and RDT-negative individuals ( p value = 0.272). The highest number of attendees screened was children in the paediatric outpatient department and paediatric ward, 62% (507/810), with RDT positivity rate of 17% (91/507). We found the highest RDT positivity rate of 51% (19/37) in the male medical ward. Conclusions: This study shows that RDT is a useful tool in promoting prompt diagnosis and management of malaria and though children form a majority of hospital attendees and malaria infections, the frequency of malaria detection may be higher in adults as compared to children.